The Effect of Organizational Culture and Commitment to Performance of Employees with Working Satisfaction as Moderation Variables in Pt. Bank Mandiri (Persero) Area Medan (Global Journal of Management and Business Research, 2018)
The banking climate in the current era of economic globalization has caused all banks including Bank Mandiri to compete to be the best. One of them is by improving organizational performance through improving employee performance. One of the factors of success in achieving the target of lending as an indicator of organizational performance is largely determined by the performance of employees. Improvement in employee performance is absolutely necessary to pay attention to several aspects including organizational culture, organizational commitment and job satisfaction. This research used a quantitative research with the population are employees of PT. Bank Mandiri (Persero), Tbk Medan Business Banking Area Imam Bonjol, totaling 40 people and the population as research samples. Data analysis used to test the effect of intervening variables is used path analysis. Organizational culture and organizational commitment have a positive effect on employee performance at PT. Bank Mandiri (Persero), Tbk Medan Imam Bonjol Business Banking Area. Organizational culture and organizational commitment have a positive effect on employee job satisfaction at PT.
Keywords: organizational culture; commitment; job satisfaction; employee performance